2019
DOI: 10.1128/aac.00904-19
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Metabolomic Polymorphism among Experimentally Selected Paromomycin-Resistant Leishmania donovani Strains

Abstract: Understanding the mechanism(s) underpinning drug resistance could lead to novel treatments to reverse the increased tolerance of a pathogen. In this study, paromomycin (PMM) resistance (PMMr) was induced in three Nepalese clinical strains of Leishmania donovani with different inherent susceptibilities to antimony (Sb) drugs by stepwise exposure of promastigotes to PMM. Exposure to PMM resulted in the production of mixed populations of parasites, even though a single cloned population was used at the start of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The copyright holder for this preprint this version posted January 6, 2021. ; https://doi.org/10.1101/2021.01.05.425522 doi: bioRxiv preprint Whole genome sequencing is a powerful tool to identify molecular changes accompanying DR development in pathogens (7) (8,32). In this study, in-depth genomic analysis revealed that TCMDC-143345 resistant lines were characterized by several aneuploidy changes, CNVs (see discussion in supplementary text) and SNPs.…”
Section: Discussionmentioning
confidence: 87%
“…The copyright holder for this preprint this version posted January 6, 2021. ; https://doi.org/10.1101/2021.01.05.425522 doi: bioRxiv preprint Whole genome sequencing is a powerful tool to identify molecular changes accompanying DR development in pathogens (7) (8,32). In this study, in-depth genomic analysis revealed that TCMDC-143345 resistant lines were characterized by several aneuploidy changes, CNVs (see discussion in supplementary text) and SNPs.…”
Section: Discussionmentioning
confidence: 87%
“…Next, the antiparasitic activity of APC12, APC14 and APC16 against three Nepalese L. donovani clinical isolates with different inherent susceptibilities to antimony, reflective of strains present in endemic communities in the ISC, was tested. We found that the Sb-S, Sb-I and Sb-R [14] strains were also killed by the APC analogues and that efficacy was influenced by alkyl carbon chain length. APC16 and APC12 were the least and most toxic with death occurring below CMC for APC12-and APC14-treated Sb-S and Sb-I promastigotes, and above CMC for APC16-treated Sb-R promastigotes and amastigotes (Table 2 and Figure S2).…”
Section: The Effect Of Varied Alkyl Carbon Chain Lengths Of Apcs Agaimentioning
confidence: 89%
“…MHOM/NP/02/BPK087/0cl11 (Sb intermediate, Sb-I) and MHOM/NP/02/BPK275/0cl18 (Sb resistance, Sb-R [13]). In addition, Milt-resistant parasites raised against these three Sb sensitivity backgrounds [14] and the Sb-sensitive strain (MHOM/ET/67:LV82) was also used in studies. Luciferase expressing promastigotes for the LV82 and Nepalese strains were prepared using previously published methods and the integrative construct (a gift from Dr D.F.…”
Section: Animals and Parasitesmentioning
confidence: 99%
“…A Nepalese strain of L. donovani had a high natural resistance to PR and increased resistance to NO was noted. PR resistance was shown to be associated with lipidomic and metabolomic strain-specific changes [ 99 ]. A recent study using chemically induced mutagenesis identified a putative calcium dependent protein kinase (LinJ.33.1810) as a potential resistance marker [ 56 ].…”
Section: Benchmark Drugs For Leishmaniasismentioning
confidence: 99%